Moscow International University Ranking “The Three University Missions” in the Global Educational Space - I. E. Zadorozhnyuk; V. M. Kalashnik; S. V. Kireev (Высшее образование в России, 2018)
This paper characterizes the national version of international university ranking as a narrow segment of social technologies. The authors dwell on the 17 indicators of the Moscow International University Ranking (MosIUR) “The Three University Missions” presented in three groups: Education (total weighed 45%), Research (25%), University & Society (30%). The role of the MosIUR in an adequate assessment of the global education system has been specified. The ranking method in MosIUR includes new elements, which enable to relate education sphere to the other social spheres.